Institutionalizing Internal Mediation: Strengthening the Medical Committee in Indonesian Hospitals - Joko Susilo; Anggraeni , Happy Yulia (Research Horizon, 2025)
Medical disputes in hospitals are frequently resolved through external channels, such as litigation or third-party mediation, imposing substantial burdens related to cost, time, and reputational risk on healthcare professionals and institutions. This study examines the critical urgency of strengthening the medical committee’s role as an internal mediator in resolving such disputes, utilizing a juridical-normative approach and extensive literature analysis. The study emphasizes the medical committee’s strategic position, which possesses technical clinical competence, professional ethical insight, and internal legitimacy necessary to mediate conflicts objectively, fairly, and transparently. Findings suggest that a stronger mediative role for the medical committee inversely correlates with the potential for disputes to escalate into litigation, thereby reducing administrative burdens and risks. Strengthening this function offers significant benefits, including risk mitigation, enhanced patient trust, reinforced ethical culture, accelerated restorative resolution, and a foundation for developing robust internal hospital regulations. The study recommends mandatory capacity building in mediation, communication, and health law for committee members, coupled with systematic monitoring mechanisms. This research expands the discourse on the committee’s mediative function practically, it offers an effective internal dispute resolution model for Indonesian hospitals.